Pengaruh Perawatan Condenser Terhadap Tekanan Condenser Di STG Blok 2 PLTGU Tambak Lorok - Harun Al Rosyid; Retno Aita Diantari; Andik Susilo (Sekolah Tinggi Teknik - PLN, 2016)
Condenser is one of the important tools in PLTGU Pond Lorok. Condenser is a heat exchanger that serves to condense the steam turbine output becomes condensate water which would then be circulated back into water filler with sea water as coolant medium. The increase in condenser pressure showed a decrease in the performance of the condenser. Therefore it is necessary for cleaning the condenser. Cleaning the condenser in the online condition can be done in an effort to lower the condenser pressure. From the condenser cleaning results during March and April condenser pressure can be lowered by 1.1 mmHg Abs - 4.3 mmHg Abs. With the reduction in the condenser pressure of ± 4 mm Hg Abs then the power turbine will rise by 1 MW, it indicates that the unit more efficient.